Usefulness of PCM in building applications focusing on envelope heat exchange – Energy saving considering two scenarios. (March 2022) - Kalbasi, Rasool
Abstract: In this study, to reduce energy consumption in conventional buildings in Iran, the technique of adding phase change material (PCM) to walls and ceilings was used. Two zones from the hot region and two zones from the cool region were selected. Five PCMs (PCM-20 to PCM-24) were selected so that their melting temperatures ranged from 20 to 24 °C. The results showed that the effect of PCM on heat exchange in winter and summer can be quite the opposite. The appropriate PCM was selected in two scenarios. Due to the concern of high electricity demand in Jun, Jul, Aug, and Sep, in scenario A, the energy consumption reduction in this period was focused. In scenario B, according to the annual analysis, the appropriate PCM was selected. For hot zones, PCM-24 managed to pass the requirements of both scenarios. For the first region, using PCM-24 resulted in energy-saving by 13.5 and 30 kWh . m - 2 in scenarios A and B, respectively. For the second region, these figures were 9.8 and 19.8 kWh . m - 2 . For cool regions, PCM-20 and PCM-21 performed well in winter, but neither could meet the requirements of scenarios A and B. For these areas, PCM-23 and PCM-24 performed well in both scenarios (although not well in the winter). In the third and fourth regions (cool climtes), under the best conditions, the addition of PCM resulted in energy-saving by 21 and 21.7 kWh . m - 2, respectively.